Visualize this : the FlowingData guide to design, visualization, and statistics - Yau, Nathan, ....- (Indianapolis (Ind.) : Wiley Pub., 2011)
There are lots of books on visualization that describe best practices and design concepts, but what do you do when it comes time for you to actually make something? If you don't know how to use the software in front of you, the abstract isn't all that useful. And with growing amounts of data, it's becoming more important to be able to make sense of and communicate with it all. In Visualize This, Nathan Yau teaches you how to create graphics that tell stories with real data, and you'll have fun in the process. Learn to make statistical graphics in R, design in Illustrator, and create interactive graphics in JavaScript and Flash & Actionscript. Yau draws from his experience as a graduate student in statistics and his work with major news organizations for an engaging, data-first approach. After all, visualization is about the data it's based on. Chapters group examples and tutorials by data type and take you through the process of data exploration and analysis, to visuals, and finally, to a graphic that is fit for publication for print and online. Read the book cover-to-cover, or keep it on your desk as a reference for your data projects. Pages are in full color with tons of graphics to inspire and to help you learn visually.
Includes bibliographical references and index.
Keywords: FlowingData; Design; Graphic methods -- Computer programs; Statistics -- Graphic methods -- Data processing; Statistieken